Veno-Arterial Extracorporeal Membrane Oxygenation for Patients Undergoing Heart Transplantation: A 7-Year Experience - Hou, Jun-yi; Li, Xin; Yang, Shou-guo; Zheng, Ji-li; Ma, Jie-fei; Su, Ying; Zhang, Yi-jie; Guo, Ke-fang; Tu, Guo-wei; Luo, Zhe (Frontiers in Medicine, 2021)
Abstract Objective: Primary graft dysfunction (PGD) is the leading cause of early death after heart transplantation. Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) can provide temporary mechanical circulatory support and time for functional recovery of the transplanted heart. The purpose of this study was to analyze the timing and prognoses of VA-ECMO in patients with severe PGD after heart transplantation. Methods: A total of 130 patients underwent heart transplantation at Zhongshan Hospital Affiliated with Fudan University between January 2014 and December 2020. All patients received basiliximab immunoinduction and a classic double vena cava anastomosis orthotopic heart transplantation. Among them, 29 patients (22.3%) developed severe PGD in the early postoperative period. VA-ECMO was performed in patients with difficulty weaning from cardiopulmonary bypass (CPB) or postoperative refractory cardiogenic shock. Patients were divided into two groups according to whether or not they were successfully weaned from VA-ECMO (patients who survived for 48 h after weaning and did not need VA-ECMO assistance again). The perioperative clinical data were recorded, and all patients were followed up until discharge. Early outcomes were compared between groups. Results: A total of 29 patients with VA-ECMO support after heart transplantation were included in this study. The proportion of patients receiving VA-ECMO was 22.3% (29/130). Nineteen patients (65.5%) needed VA-ECMO due to difficulty with weaning from CPB and 10 patients required VA-ECMO for postoperative cardiogenic shock. Nineteen patients (65.5%) were successfully weaned from VA-ECMO. Overall in-hospital mortality of VA-ECMO support patients was 55.2%. The main causes of death were ventricular fibrillation (four cases), major bleeding (three cases), infection (four cases), and graft failure (five cases). Conclusion: Despite advances in heart transplantation, severe PGD remains a lethal complication after heart transplantation. At present, the treatment for severe PGD after heart transplantation is a challenge. VA-ECMO provides an effective treatment for severe PGD after heart transplantation, which can promote graft function recovery.